The Impact of Reward and Punishment on Teacher Performance, Job Satisfaction, and Loyalty: A Literature Review - Yusuf Effendi; Oki Dermawan; Dina Amalia (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
Reward and punishment are human resource management strategies widely implemented in educational organizations to improve teacher performance. This study aims to analyze the impact of reward and punishment on teacher performance, job satisfaction, and loyalty based on a literature review from various recent national and international journals. The method used is a literature review, examining and analyzing relevant scientific articles. The results show that reward has a positive and significant impact on improving teacher performance, job satisfaction, and loyalty to the educational institution. Rewards, both financial and non-financial, such as professional recognition and career development opportunities, have been proven to enhance both intrinsic and extrinsic motivation of teachers. Meanwhile, punishment has a more complex impact; in certain contexts, it can improve discipline and performance, but if applied disproportionately, it can potentially decrease satisfaction and loyalty. Therefore, the application of reward is more recommended as the main strategy in educational management, while punishment should be used selectively, fairly, and educationally. These findings have implications for school principals and education managers in designing effective and sustainable teacher performance management policies.